The Norwegian species of Copidosoma Ratzeburg (Hymenoptera: Chalcidoidea: Encyrtidae) - Japoshvili, George; Hansen, Lars Ove; Guerrieri, Emilio (Zootaxa, 2013)
The species of Copidosoma Ratzeburg (Hymenoptera: Encyrtidae) are reviewed for Norway. Sixteen species are recognized, of which one, Copidosoma longicaudata sp. nov., is newly described, illustrated and compared with closely related species. Seven species represent new distribution records for Norway—C. aithyia (Walker), C. genale (Thomson), C. herbaceum Mercet, C. primulum (Mercet), C. radnense Erdős, C. thebe (Walker) and C. truncatellum (Dalman). An illustrated dichotomous key for the identification of both sexes of Norwegian Copidosoma is presented.